In2O3 / 2D-MoS2 heterojunction thin film material and preparation method and application thereof

By depositing In2O3 film using magnetron sputtering method on the surface of 2D-MoS2, a p-n-type heterojunction film material was formed, and the problems of long response/recovery time and poor selectivity of pure 2D-MoS2 at room temperature were solved, and the NOx gas was achieved High sensitivity and fast response detection.

CN117626196BActive Publication Date: 2025-02-25INST OF SENSOR TECH GANSU ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311586542.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2025-02-25
Estimated Expiration
2043-11-24

AI Technical Summary

Technical Problem

In the prior art, pure 2D-MoS2 faces problems such as insufficient sensitivity, long response/recovery time at room temperature and poor selectivity without external light or temperature.

Method used

In2O3 film was prepared on the 2D-MoS2 surface by magnetron sputtering method to form a p-n-type heterojunction film material. The method includes depositing In2O3 film by magnetron sputtering method on the 2D-MoS2 surface, optimizing the sputtering parameters to form a high-quality heterostructure.

Benefits of technology

High sensitivity detection and rapid response/recovery of NOx gas at room temperature is achieved, avoiding dependence on external light or temperature, and improving the selectivity and service life of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117626196B_ABST
    Figure CN117626196B_ABST
Patent Text Reader

Abstract

The invention discloses an In 2 O 3 / 2D‑MoS 2 Heterojunction thin film material and preparation method and application thereof, the preparation method comprising the following steps: using magnetron sputtering method to deposit 2D-MoS 2 Surface preparation 2 O 3 The film forms a heterojunction thin film material; wherein, during magnetron sputtering, the gas flow is 15-25sccm, the gas pressure is 1-2Pa, the power is 10-20W, and the sputtering time is 25-35s. The present invention uses a method combining physical vapor deposition and chemical vapor deposition to design and construct In 2 O 3 / 2D‑MoS 2 Heterojunction. By optimizing the thickness, interface structure, interface quality, surface morphology, uniformity and crystallinity of heterojunction films, a new method was obtained that can significantly improve the gas (NO x ) Sensitivity of heterostructures In 2 O 3 / 2D‑MoS 2 Gas sensing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thin film materials, and in particular to an In2O3 / 2D-MoS2 heterojunction thin film material and a preparation method and application thereof. Background Art

[0002] The rapid development of the world economy has generated a large amount of NO in industrial production and urban life. x Gas emissions mainly come from waste gas emissions from the chemical industry and exhaust gas from motor vehicles in urban life. x Concentrations exceeding the human limit can cause a series of respiratory diseases such as cancer, asthma, pneumonia, bronchitis, etc. Excessive NO2 concentration in the air tends to produce acid rain. x The toxicity and danger of gases urgently require an accurate detection method to detect the concentration of harmful gases in the environment.

[0003] Traditional detection of NO x There are many methods for detecting gas, such as chemiluminescence, chromatography, infrared, etc. These detection methods have advantages in sensitivity and detection limit, but their working devices are complex and cost-effective, which is not conducive to real-time on-site detection in actual environments. Relatively speaking, most chemical sensors can meet the requirements of simplicity, rapidity, and on-site monitoring required by the environment. According to the different gas-sensing mechanisms, chemical sensors are mainly divided into surface acoustic wave chemical sensors, optical fiber chemical sensors, electrochemical sensors, and semiconductor chemical sensors. Among them, semiconductor chemical sensors have attracted widespread attention due to their simple synthesis process, high cost-effectiveness, and convenient operation.

[0004] At present, the research on semiconductor gas sensor materials is mainly based on metal oxide semiconductors, organic semiconductors and two-dimensional materials such as graphene. Organic semiconductor material sensors are easily affected by the operating temperature and voltage; graphene has good conductivity, but has disadvantages such as low sensitivity, poor stability and short service life; metal oxide semiconductor materials have advantages such as high sensitivity, good selectivity and good stability, but require high test temperature and high energy consumption. Therefore, it is necessary to explore and study new NO sensors with high sensitivity, excellent selectivity, fast response and recovery, and low power consumption. x The focus of gas sensors has begun to shift towards regulating the properties of the sensitive materials themselves.

[0005] Molybdenum disulfide (MoS2) is a typical two-dimensional semiconductor material. Its single-layer or thin-layer two-dimensional lattice structure has a large specific surface area. Its fully exposed surface shows the largest surface effect, making it the most promising candidate for gas sensing materials. According to first-principles calculations, MoS2 is sensitive to nitrogen oxides, especially in the detection of NO2 gas. However, in the absence of external light or temperature, pure 2D-MoS2 still faces the challenges of improving sensitivity, accelerating response / recovery kinetics at room temperature, and the poor selectivity common to traditional two-dimensional materials. Summary of the invention

[0006] In order to solve the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide an In2O3 / 2D-MoS2 heterojunction thin film material and a preparation method and application thereof, so as to solve the problem that pure 2D-MoS2 needs to improve sensitivity and accelerate response / recovery dynamics at room temperature in the absence of external light or temperature.

[0007] The technical solution of the present invention to solve the above technical problems is as follows: Provide an In2O3 / 2D-MoS2 heterojunction thin film material, and the preparation method thereof comprises the following steps:

[0008] The magnetron sputtering method is used to prepare In2O3 thin film on the surface of 2D-MoS2 to form a heterojunction thin film material; wherein, during magnetron sputtering, the gas flow is 15-25sccm, the gas pressure is 1-2Pa, the power is 10-20W, and the sputtering time is 25-35s.

[0009] The beneficial effects of the present invention are as follows: molybdenum disulfide MoS2 exhibits good nitrogen dioxide detection performance due to its adjustable band gap, S-Mo-S layer attached by weak van der Waals force, and high interaction ability with adsorbed gas molecules. However, two-dimensional molybdenum disulfide (2D-MoS2) has a slow response / recovery time when used as a gas-sensitive material to detect nitrogen dioxide gas, and sometimes requires heating or illumination to shorten the response / recovery time. The present invention prepares an In2O3 film on the surface of 2D-MoS2 by magnetron sputtering to form a pn-type heterostructure. In2O3 is an n-type semiconductor with a wide band gap (3.55-3.76eV) and excellent thermal stability, but when using this material to detect gas, a high operating temperature is required, and only relatively high concentrations of gas (ppm level) are detected. Two-dimensional molybdenum disulfide (2D-MoS2) and In2O3 form a pn heterostructure, and the formation of a heterogeneous interface provides more active sites for the gas, which can promote gas diffusion and faster electron transfer. In addition, the pn heterostructure formed at the interface of the two will generate an internal electric field. The gas molecules capture electrons from the n-type material and reduce its electron concentration. The excess holes return to the surface of the p-type material. This adsorption process greatly reduces the potential barrier, increases the conductivity of the heterostructure, accelerates electron transfer, and thereby improves the sensitivity and response recovery speed of the gas sensor.

[0010] On the basis of the above technical solution, the present invention can also be improved as follows:

[0011] Furthermore, during magnetron sputtering, the gas flow was 20 sccm, the gas pressure was 1.5 Pa, the power was 15 W, and the sputtering time was 30 s.

[0012] The beneficial effects of adopting the above further technical solution are: the pn heterostructure is composed of two materials, namely 2D-MoS2 and In2O3. 2D-MoS2 is a p-type material that lacks electrons, while In2O3 is an n-type material that can provide excess electrons. When these two materials come into contact, a pn heterostructure will be formed. Magnetron sputtering is a technology that deposits materials on a substrate. By using a magnetic field, electrons and ions can be separated and their movement can be controlled. Magnetron sputtering can control the properties of the deposited material through the selection of substrate and target materials and their processing conditions. By adjusting these parameters, the thickness, interface structure, interface quality, surface morphology, uniformity and crystallinity of the heterojunction film can be controlled in multiple dimensions. When magnetron sputtering, the parameters are optimized as follows: air flow of 20sccm, air pressure of 1.5Pa, power of 15W, and sputtering time of 30s, which can significantly improve the NO x Gas sensitivity and response / recovery performance.

[0013] Furthermore, 2D-MoS2 is prepared by the following method: under catalyst conditions, a chemical deposition method is used to carry out sulfurization on the surface of the Mo film to obtain 2D-MoS2.

[0014] Furthermore, a carrier gas is introduced into a container containing a carrier carrying a Mo film, sulfur powder and a catalyst, and a deposition reaction is carried out at 650-800° C. for 10-30 minutes, preferably 700° C. for 30 minutes.

[0015] Furthermore, the mass ratio of the catalyst to the sulfur powder is 0.5-1:1-3; preferably, the catalyst is sodium chloride; and the mass ratio of the catalyst to the sulfur powder is 1:2.

[0016] Furthermore, the carrier gas is a mixture of argon and hydrogen, and the flow rates of argon and hydrogen are 15-25 sccm and 2-8 sccm respectively; preferably, the flow rate of argon is 20 sccm and the flow rate of hydrogen is 5 sccm.

[0017] A gas sensor comprises the In2O3 / 2D-MoS2 heterojunction thin film material prepared above.

[0018] The prepared In2O3 / 2D-MoS2 heterojunction thin film material or the above-mentioned gas sensor is used to detect NO x Gas applications.

[0019] The above NO x The gas is NO2.

[0020] The present invention has the following beneficial effects:

[0021] The present invention designs, constructs and prepares a large-area continuous In2O3 / 2D-MoS2 heterojunction new material by combining magnetic sputtering with chemical phase deposition. 2D-MoS2 and In2O3 form a pn heterostructure, and the interface characteristics of the heterostructure can improve the gas sensing performance, which is mainly the result of the synergistic effect of the internal electric field, electron migration and heterojunction interface of the heterostructure.

[0022] The present invention optimizes the thickness, interface structure, interface quality, surface morphology, uniformity and crystallinity of the heterojunction film to achieve the goal of NOx at room temperature without ultraviolet light. x The purpose of high sensitivity and fast response of base gas is to BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the preparation process of the In2O3 / 2D-MoS2 heterojunction thin film material of the present invention.

[0024] Figure 2 This is the relationship between the thickness of the Mo film and the sputtering time.

[0025] Figure 3 Schematic diagram of the process of preparing 2D-MoS2 structure film by chemical vapor deposition.

[0026] Figure 4 This is the SEM image of 2D-MoS2 thin film material.

[0027] Figure 5 This is the Raman spectrum of 2D-MoS2 thin film material.

[0028] Figure 6 A diagram characterizing the characteristics of the In2O3 / 2D-MoS2 heterojunction.

[0029] Figure 7 This is a surface scan of In2O3 / 2D-MoS2 heterostructure thin film materials.

[0030] Figure 8 Schematic diagram of the gas sensing test system. DETAILED DESCRIPTION

[0031] The following examples are only used to explain the present invention and are not intended to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0032] Embodiment 1:

[0033] An In2O3 / 2D-MoS2 heterojunction thin film material, the preparation process flow chart is shown in Figure 1 , the specific preparation process is as follows:

[0034] Step 1: Preparation of Mo seed layer

[0035] Mo thin film was prepared by magnetron sputtering. The specific process is as follows:

[0036] The Si substrate with oxide layer was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 15 minutes in turn, and the surface of the Si substrate was blown dry with high-purity nitrogen. The cleaned Si substrate was placed in a magnetron sputtering vacuum chamber for sputtering. During the sputtering process, the growth rate, thickness and crystal quality of the Mo film were controlled by controlling the gas pressure, airflow, power and time. The specific optimization process is shown in Table 1, and the relationship between the thickness of the Mo film and the sputtering time is shown in Figure 2 After comprehensive consideration, the optimized process parameters were obtained as follows: gas flow of 20 sccm, gas pressure of 1 Pa, power of 10 W, and sputtering time of 60 s.

[0037] Table 1 Thickness of Mo films under different sputtering conditions

[0038]

[0039] The thickness of the Mo film in Table 1 was obtained by measuring three points on the film surface during the measurement process and taking the average value.

[0040] Step 2: Use chemical vapor deposition to sulfurize the Mo film under the action of catalyst NaCl to prepare a 2D-MoS2 structure film. The specific process is:

[0041] The Mo film on the Si substrate prepared in step 1 and the quartz boat containing sulfur powder and sodium chloride are placed in the quartz tube of the deposition system, the main furnace is turned on for heating, and the carrier gas is introduced. When the heating temperature reaches the set value of 700°C, the main furnace is pushed to the quartz tube sample to carry out the deposition reaction (such as Figure 3 As shown). After the deposition reaction is completed, the main furnace is immediately removed from the quartz tube sample to allow the sample to cool naturally. In the vapor deposition stage, the molecular layer number, film thickness, arrangement mode, and crystal quality of the 2D-MoS2 thin film material are controlled by adjusting the mass ratio of sodium chloride to sulfur powder, carrier gas flow, main furnace temperature, and sulfurization deposition time to obtain a 2D-MoS2 thin film material with large area, continuous, and high active sites.

[0042] The above-mentioned control of each parameter is specifically as follows:

[0043] The mass ratio of sodium chloride to sulfur powder is 0.5:1, 1:1, 1:2, and 1:3.

[0044] The carrier gas flow rates were: flow ratios of hydrogen to argon were 1:2, 1:4, and 1:8.

[0045] The main furnace temperature is: 650℃, 700℃, 750℃, 800℃.

[0046] The deposition time is: 10min, 20min, 30min.

[0047] Through the control results of the above parameters, it can be seen that when the amount of sodium chloride is too little, the 2D-MoS2 film cannot be formed, and when the amount of sodium chloride is too much, the 2D-MoS2 film is unevenly formed and thicker. When the hydrogen flow rate in the carrier gas is too little, it is not easy to form a 2D-MoS2 film. When the hydrogen flow rate is too much, the reaction rate is too fast, it is not easy to form a two-dimensional material, the film is thicker, and the surface is uneven. When the temperature of the main furnace is too low, the film quality is poor. When the temperature is too high, the reaction is too fast and difficult to control. When the deposition time is short, the reaction is incomplete, and the sediment has not grown completely on the wafer surface. The deposition time is too long, the film is thicker, and it is not easy to obtain a two-dimensional material. After comprehensive analysis, the optimized process parameters are finally obtained: NaCl 1g, sulfur powder 2g, Ar gas 20sccm, H2 gas 5sccm, reaction temperature 700℃, reaction time 30min.

[0048] In addition, Raman spectroscopy (Raman), scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), cross-sectional and surface transmission electron microscopy (TEM) and other analytical methods were used to characterize the interface structure, chemical composition, surface morphology and uniformity of the 2D-MoS2 film. The SEM characterization of the 2D-MoS2 film material is shown in Figure 4 ; Raman spectrum see Figure 5 .

[0049] Depend on Figure 4 From 4-1 and 4-2, we can see that the reaction film surface is very uniform, and the surface elements can be seen from the surface scans of 4-3 and 4-4.

[0050] from Figure 5 The characteristic peaks of 2D-MoS2 can be seen, proving that a 2D-MoS2 film is formed after sulfurization.

[0051] Step 3: Controllable construction of In2O3 / 2D-MoS2 heterostructure

[0052] The In2O3 film was prepared on the surface of 2D-MoS2 by magnetron sputtering to form a heterostructure. The specific process is as follows:

[0053] The 2D-MoS2 film obtained after the parameters are optimized in step 2 is placed in a magnetron sputtering vacuum chamber, and the In2O3 target is sputtered using a radio frequency power supply. The growth rate and crystallization quality of In2O3 on the surface of the 2D-MoS2 film are controlled by adjusting the gas pressure, airflow, and power. Finally, the optimized process parameters are obtained: airflow of 20sccm, gas pressure of 1.5Pa, power of 15W, and sputtering time of 30s.

[0054] Finally, the interface structure of 2D-MoS2 and In2O3 heterostructure is further optimized through characterization analysis, and it is expected to achieve controllable construction of In2O3 / 2D-MoS2 heterostructure.

[0055] Scanning electron microscopy (SEM), X-ray diffractometer (XRD), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), transmission electron microscopy (TEM) and other analytical methods were used to characterize the crystallinity, film thickness, electronic structure, composition, chemical state, interface effect, surface flatness and uniformity of In2O3 / 2D-MoS2 heterostructure films.

[0056] Figure 6A diagram characterizing the characteristics of the In2O3 / 2D-MoS2 heterojunction; the black part represents the 2D-MoS2 film, and the black surface granular material is In2O3; the Spectrum1 spectrum shows In ions, while the Spectrum2 spectrum shows Mo ions and S ions.

[0057] Figure 7 This is a surface scan of In2O3 / 2D-MoS2 heterostructure thin film materials. Figure 6 It can be seen that after the heterojunction is formed, the surface elements are only Mo, S, In, and O. From the interface diagram, it can be seen that there are obviously two layers of film, the first layer is MoS2, and the second layer is In2O3. This is also illustrated by Spectrum1, Spectrum2, and Spectrum3.

[0058] Embodiment 2:

[0059] Preparation of gas sensor: In2O3 / 2D-MoS2 heterojunction thin film material is placed on a laser direct writer to process Au electrodes. The processed electrodes are connected to the gas sensing test system through leads to conduct NO x The response / recovery and sensitivity test of the base gas under different gas concentrations is completed on the dynamic system. The specific process is as follows:

[0060] 1. Preparation of gas-sensing electrodes

[0061] (1) First, a gold film with a thickness of about 1 μm is uniformly coated on the In2O3 / 2D-MoS2 heterojunction film by magnetron sputtering;

[0062] (2) Spin-coat the plated gold film with photoresist on a photoresist spin coater, photoresist model: AZ5214, spin coating thickness: 1-2 μm;

[0063] (3) Photoresist pre-baking, 100°C for 5 min;

[0064] (4) Au electrode processing was performed on a laser direct writer with a laser energy of 80%;

[0065] (5) After photolithography, add 10% NaOH for development for 2 minutes;

[0066] (6) After development, the thin film on the silicon substrate is placed on an etcher and etched at an angle of 130° for 15 minutes.

[0067] 2. Gas sensitivity test

[0068] The gas sensitivity test in the present invention is to study the gas-sensitive response of the heterogeneous structure to the target gas at room temperature. During the test, the ambient temperature is room temperature 25°C and the relative humidity is 30%. The volume of the injected NO2 gas is controlled by using a precise micro-injection needle (the injected volume is in a gradient, 0.01ppm, 2ppm, 3ppm...100ppm, and the specific concentration is as follows The conversion concentration), and the concentration of the gas is calculated and controlled according to the volume of the chamber. When a certain amount of target gas is injected, the resistance of the test electrode changes, and the signal is input into the computer through the connected device to further obtain the gas-sensitive dynamic response curve. When the injection is completed, the valve that is opened and closed is used to refill a large amount of air into the chamber through the suction force of the vacuum pump to restore the initial resistance of the test electrode.

[0069] The above test process is carried out in a sealed device (the specific gas-sensitive test system diagram can be seen in Figure 8 ), NO2 gas is introduced for testing, but the sealed container is not in a vacuum state, but is carried out in an air atmosphere, so the concentration is converted relative to air, that is, the concentration of NO2 gas relative to air is converted from high to low, namely 100, 50, 30, 10, 5, 3, 1, 0.5, 0.3, 0.1, 0.03, and 0.01ppm.

[0070] Generally, the performance of gas sensing electrodes is evaluated by three main parameters: response value (sensitivity value), response time and recovery time.

[0071] (1) The response value (sensitivity value) is the ratio of the change in sensor resistance before and after the external test conditions are added, which can directly reflect the gas sensing performance of the material. The sensitivity calculation formula is as follows:

[0072] S=R a / R g

[0073] Among them, R a Sheet resistance measured for electrodes stabilized in air atmosphere;

[0074] R g is the transient sheet resistance measured when the electrode is exposed to the target atmosphere.

[0075] (2) Response time is the time taken for the electrode to reach the final equilibrium state and 90% of the maximum sensitivity value after exposure to the target atmosphere.

[0076] (3) Recovery time is the time taken for the resistance value to change by 90% when the target environment is removed.

[0077] From the above detection, it can be known that the sensor made of In2O3 / 2D-MoS2 heterojunction thin film material provided by the present invention has a NO2 detection concentration range of 0.01-100ppm, a NO2 sensitivity S>80%, and a response / recovery time of less than 50 / 100s. The sensor has good response and recovery characteristics to 0.05-100ppm NO2. At room temperature, the response value of the gas sensor of the present invention to 1ppm NO2 is 90%, and the response / recovery time is 20 / 45s.

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An In2O3 / 2D-MoS2 heterojunction thin film material detects NO at room temperature without UV illumination x Application in gas, characterized in that The In2O3 / 2D-MoS2 heterojunction thin film material is prepared by the following method: preparing an In2O3 thin film on the surface of 2D-MoS2 by a magnetron sputtering method to form a heterojunction thin film material; Among them, during magnetron sputtering, the gas flow is 20sccm, the gas pressure is 1.5Pa, the power is 15W, and the sputtering time is 30s; 2D-MoS2 is prepared by the following method: a carrier gas is introduced into a container containing a carrier carrying a Mo thin film, sulfur powder, and a catalyst, and a deposition reaction is carried out at 700°C for 30 minutes to prepare 2D-MoS2; the catalyst is sodium chloride; the carrier gas is a mixture of argon and hydrogen, and the flow rates of argon and hydrogen are 20 sccm and 5 sccm respectively; the mass ratio of the catalyst to the sulfur powder is 1:2; The Mo film was prepared by magnetron sputtering. During magnetron sputtering, the gas flow was 20 sccm, the gas pressure was 1 Pa, the power was 10 W, and the sputtering time was 60 s.

2. The use according to claim 1, characterized in that: NO x The gas is NO2.

Citation Information

Patent Citations

  • Method for preparing molybdenum disulfide based on alkali metal solution catalysis

    CN110886019A

  • Low-dimensional layered molybdenum disulfide film material and preparation method thereof

    CN115011925A